4x-2(x-4)=-6+5x+8

Simple and best practice solution for 4x-2(x-4)=-6+5x+8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-2(x-4)=-6+5x+8 equation:



4x-2(x-4)=-6+5x+8
We move all terms to the left:
4x-2(x-4)-(-6+5x+8)=0
We add all the numbers together, and all the variables
4x-2(x-4)-(5x+2)=0
We multiply parentheses
4x-2x-(5x+2)+8=0
We get rid of parentheses
4x-2x-5x-2+8=0
We add all the numbers together, and all the variables
-3x+6=0
We move all terms containing x to the left, all other terms to the right
-3x=-6
x=-6/-3
x=+2

See similar equations:

| 4+1+8a+8a=4a-5+7a | | n-18=19 | | 7+2n=7n-8 | | x/9+13=0 | | -7(k+9)=9(k+-5)+-14k | | 8-4(f-3)=0 | | -7(k+9)=9(k+-5)-14k | | 5+7x+x=1+7x+1 | | 14n=-126 | | -7(x+6)-3(3x-3)=-65 | | 9k-16=52 | | g+143=1000 | | 33/4=r=1/8 | | №23x=10 | | 4z-3(z-6)=3=2z | | -4m-8=54 | | 2-2m=-20 | | 14-x=4+2x | | 21=-7×n | | 28j=952 | | 95x-15=-12 | | -27d=270 | | -8(8x-7)=440 | | 4^5x-9=(1/27)^2x-8 | | 5(3-e)+10=0 | | h+577=952 | | 8/11n=64 | | X=1+1.2x | | -10k+6k+k×10=60 | | 8/11n=74 | | y-52=174 | | 3x+-9=(10+x) |

Equations solver categories